Pedagogika zdrowia – sekcja judo jako miejsce „uczenia się zdrowia” mężczyzn w różnym wieku = Health pedagogy - Section judo as a space of "health learning" men of different ages - Drumińska, Ewelina; Wilczyńska, Sylwia; Pujszo, Małgorzata; Stępniak, Robert (Journal of Education, Health and Sport, 2015)
Drumińska Ewelina,Wilczyńska Sylwia, Pujszo Małgorzata, Stępniak Robert. Pedagogika zdrowia – sekcja judo jako miejsce „uczenia się zdrowia” mężczyzn w różnym wieku = Health pedagogy - Section judo as a space of "health learning" men of different ages. Journal of Education, Health and Sport. 2015;5(10):79-90. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.32061 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2810%29%3A79-90 https://pbn.nauka.gov.pl/sedno-webapp/works/655268 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.08.2015. Revised 05.09.2015. Accepted: 29.09.2015. Pedagogika zdrowia – sekcja judo jako miejsce „uczenia się zdrowia” mężczyzn w różnym wieku Health pedagogy - Section judo as a space of "health learning" men of different ages Drumińska Ewelina1,Wilczyńska Sylwia1, Pujszo Małgorzata1, Stępniak Robert2 1Sekcja Kultury Fizycznej, Koło Naukowe „Wykona”, Uniwersytet Kazimierza Wielkiego Bydgoszcz, Polska 2Instytut Kultury Fizycznej, Uniwersytet Kazimierza Wielkiego, Polska Korespondencja: Stępniak Robert Ph.D Instytut Kultury Fizycznej, Uniwersytet Kazimierza Wielkiego, ul. Sportowa 2, 85-091 Bydgoszcz, Polska email: <robi1969@wp.pl> Abstrakt Objective: Poor physical activity is a problem of the young generation of Polish society. Every person should "learn to health" as a way to maintaining physical and mental fitness of all ages.The efficiency of the respiratory system may be developed in various ways by active "learning health" for example: recreational training. It was decided to check whether the assumption of the above can be implemented in judo. Material and methods: We examined the efficiency of respiratory spirometric, BMI index and distribution of body fat tissue of men of different ages who train for recreational judo. The results were compared with the results of people leading a sedentary lifestyle. Results: Were observed a significant differences between the efficiency of the respiratory system and the distribution of body fat tissue between people recreationally practicing judo at every stage of ontogeny, and peoples leading a settled life. Conclusions: Recreation judo training meets the requirements to improve the functioning of the respiratory system of people of all ages. The physical activity in this way can be considered as one of method of "learning health" Streszczenie Cel: Niska aktywność fizyczna jest problemem młodego pokolenie polskiego społeczeństwa Każdy człowiek powinien „uczyć się zdrowia” w sposób rozumiany jako dbałość o zachowanie sprawności fizycznej i umysłowej w każdym wieku. Sprawność układu oddechowego może być podtrzymywana na wiele sposobów poprzez aktywne „uczenie się zdrowia” czyli rekreacyjny trening. Postanowiono sprawdzić czy założenie powyższe można realizować w sekcji judo. Materiał i metody: Sprawdzono sprawność układu oddechowego badaniem spirometrycznym mężczyzn w różnym wieku trenującym rekreacyjnie judo, a uzyskane wyniki porównano z wynikami osób prowadzących siedzący tryb życia . Dodatkowo sprawdzono wskaźnik BMI oraz zawartości tkanki tłuszczowej Wyniki: Wykazano istotne różnice pomiędzy sprawnością układu oddechowego i dystrybucją tkanki tłuszczowej osób trenujących rekreacyjnie judo na każdym etapie ontogenezy, a studentami prowadzącymi osiadły tryb życia. Wnioski: Rekreacyjny trening judo spełnia wymogi poprawy funkcjonowania układu oddechowego osób w każdym wieku. Utrzymywanie sprawności w ten sposób można więc uznać jako jedną z możliwości „uczenia się zdrowia” Słowa kluczowe: judo, sprawność fizyczna, spirometria. Keywords: judo, physical fitness, spirometry.